DAMPAK BPNT TERHADAP KONSUMSI RUMAH TANGGA DAN POLA KONSUMSI RUMAH TANGGA PENERIMA BPNT, KECAMATAN MENGWI - Handriani, Luh Ade Yumita; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to analyze the impact of the BPNT program on household consumption and consumption patterns of BPNT recipient households in Mengwi District, Badung Regency. This research was conducted in Mengwi District, Badung Regency using a questionnaire distributed to respondents with a large sample size of 96 KPM. This study uses path analysis techniques to analyze the direct effect and Sobel test to analyze the indirect effect. Based on path analysis, the results of the study concluded that the BPNT variable had a positive and significant effect on the consumption of BPNT recipient households in Mengwi District, Badung Regency. The BPNT variable has no effect on the consumption pattern of BPNT recipient households in Mengwi District, Badung Regency. The household consumption variable has a negative and significant effect on the consumption pattern of BPNT recipient households in Mengwi District, Badung Regency. The household consumption variable did mediate the effect of the BPNT Program on the consumption pattern of BPNT recipient households in Mengwi District, Badung Regency